STRATEGI PENINGKATAN MOTIVASI DAN KEPUASAN KERJA PADA GURU SD NEGERI 2 KOPEN KECAMATAN JATIPURNO TAHUN 2025: Strategi Peningkatan Motivasi dan Kepuasan Kerja Guru Sekolah Dasar di Wilayah Pedesaan: Sebuah Studi Fenomenologi - Paryanti Paryanti; Baidi Baidi (jsd: Journal of Society and Development, 2026)
Despite frequently facing inadequate facilities and limited financial rewards, many rural elementary school teachers continue to demonstrate extraordinary dedication to their duties. This phenomenon raises a critical question regarding the sources of motivation and job satisfaction that transcend material boundaries. This study aims to explore the subjective meanings and experiences of elementary school teachers in maintaining motivation and job satisfaction within rural settings, identifying adaptive strategies used amidst resource limitations. A qualitative approach with a phenomenological design was employed. Data were gathered through in-depth interviews, participant observations, and document reviews involving eight teachers with diverse professional backgrounds. Thematic analysis was conducted following Braun and Clarke's framework to derive core themes. The results indicate that teachers maintain high levels of motivation and job satisfaction despite inadequate infrastructure and resources. Intrinsic factors, particularly the sense of purpose in the profession and moral commitment to students, emerged as the most dominant drivers. Furthermore, supportive leadership from the principal and harmonious social relationships among colleagues significantly fostered a positive work environment and institutional belonging. In contrast, extrinsic factors such as financial compensation and physical facilities did not substantially diminish the teachers' work commitment. This study suggests that enhancing collaborative work cultures, providing professional autonomy, and ensuring continuous career development are vital strategies for sustaining teacher engagement in rural primary education.